PENGARUH PENGGUNAAN MEDIA CANVA TERHADAP MINAT BELAJAR SISWA KELAS 5 SEKOLAH DASAR - Padli Ibnu Naji; Rita Kusumah (Universitas Negeri Medan, 2025)
This study aims to analyze the effect of Canva media on students' learning interest in Natural and Social Sciences (IPAS) in fifth grade elementary schools. Initial observations showed low student interest due to monotonous media use, with only 16 out of 40 students achieving the Minimum Completion Criteria (KKM). This methodology involved two meetings: one meeting without Canva media and one meeting with Canva media. Data were collected using a valid questionnaire, measuring indicators such as student attention and engagement. The results showed an increase in student learning interest from 72% to 84% after the use of Canva media. These findings indicate that Canva helps create an engaging learning environment with presentation designs, infographics, and interactive quizzes, effectively enhancing student creativity and learning outcomes.